Pemberdayaan Warga Melalui Program Rumah Layak Huni Untuk Tingkatkan Kualitas Hidup di Desa Marga Mulya - Muhammad Diva Mu’zizat; Wa Ode Asmawati (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
This study investigates the impact of Habitat for Humanity Indonesia's Decent Housing Program on improving the quality of life of poor residents in Marga Mulya Village. The research aims to evaluate the role of community empowerment through the program in increasing access to decent housing, as well as to assess its broader impacts on education, health, and the economic conditions of the beneficiaries. Using a qualitative research method with a case study approach, data were collected through in-depth interviews with program participants and key stakeholders. The findings show that the Decent Housing Program has significantly improved access to adequate and safe housing for the poor. In the field of education, improved housing conditions have created a more conducive environment for children to study, leading to greater learning motivation and better academic achievements. In terms of health, better sanitation facilities and healthier living environments have reduced the risk of infectious diseases and contributed to the residents' overall physical and mental well-being. Economically, access to stable and decent housing has reduced household expenditures on home repairs, allowing families to allocate more resources toward productive economic activities. However, the study also identified several challenges that need to be addressed to further enhance program effectiveness. These challenges include the location of housing projects that are difficult to access, which affects residents' mobility and access to public services, and issues related to the quality of construction that require continuous monitoring and improvement. Overall, the study highlights the positive contribution of the Decent Housing Program while providing recommendations for its future development.